‘Noteomielite’ accompanied by acute amaurosis (1844): an early case of neuromyelitis optica - Jarius, Sven; Wildemann, Brigitte (Journal of the neurological sciences, 2012)
So far, only very little is known about the early history of neuromyelitis optica (Devic's syndrome). Here, we discuss a then widely recognized but now forgotten 1844 report by the Genoese physician Giovanni Battista Pescetto (1806-1884) on a 42-year-old man, who simultaneously developed acute amaurosis and cervical myelitis. Pescetto's report represents the earliest account of a case of neuromyelitis optica in the Western literature known so far.